Kinerja Pegawai PT. Biofit Putra Di Pengaruhi Oleh Work Life Balance Dan Motivasi - Muchamad Bryan Pratama; Nita Kanya; Dudi Haryadi; Fajar Eryanto Septiawan (Pusat Riset dan Inovasi Nasional, 2025)
The purpose of this study was to examine the effect of Work Life Balance and Work Motivation on Employee Performance. This study used a population of 41 employees working in the Lab Clinic of PT Biofit Putra Bandung using descriptive and verification methods. The data collection technique used by the researcher was to use primary and secondary data sources in the form of questionnaires given to employees of the Lab Clinic of PT Biofit Putra Bandung. The analysis used was path analysis using SPSS software version 27 The results of this study indicate that the variables of Work Life Balance is considered quite good, Work Motivation is considered quite good and Employee Performance is considered quite good. The verification show that Work Life Balance affects Employee Performance, Work Motivation affects Employee Performance and there is an effect of Work Life Balance and Work Motivation on Employee Performance in the clinical lab section of PT. Biofit Putra.